Case Report: A Durable Response to Camrelizumab and Apatinib Combination Therapy in a Heavily Treated Small Cell Carcinoma of the Ovary, Hypercalcemic Type - Li, Guiling; Jiang, Yao (Frontiers in Oncology, 2022)
Small cell carcinoma of the ovary, hypercalcemic type (SCCOHT) is a rare and highly aggressive malignancy with a poor prognosis. Most patients experience recurrence even after surgery and chemotherapy, and there are no standard treatment options for recurrent disease. Here, we report the case of a 36-year-old woman with SCCOHT who underwent primary cytoreductive surgery without adjuvant chemotherapy and remained disease-free for 9 months. She then developed retroperitoneal lymph node metastasis and was treated with two cycles of bleomycin/etoposide/cisplatin chemotherapy. However, the disease progressed and the patient received four cycles of liposomal doxorubicin/ifosfamide chemotherapy, followed by local radiation to the enlarged retroperitoneal lymph nodes. She achieved partial remission for 13 months, after which the disease progressed again. Tumor tissues and blood samples were sent for next-generation sequencing. The results indicated a somatic SWI/SNF-related, matrix-associated, actin-dependent regulator of chromatin, subfamily A, member 4 (SMARCA4) mutation, microsatellite stability, and a tumor mutation burden of 1.0 muts/Mb without any germline mutations. An anti-PD-1 antibody, camrelizumab, and an antiangiogenic agent, apatinib, were administered, and the patient achieved partial remission for 28 months. Our study provides the first clinical evidence that the combination therapy of camrelizumab and apatinib could be an effective treatment for recurrent SCCOHT.